Joseph & Jesus. Bible-based Musicals and Contemporary Passions staged in the Public Domain: an Exploration of a Research Perspective - Klomp, Mirella (Jaarboek voor liturgieonderzoek, 2011)
Bible-based musicals and contemporary Passion performances as brought to the stage in theaters and concert halls may be seen as contemporary manifestations of religion. Over the last few years, most scholars have come to agree that a certain understanding of the secularization thesis - at least in Dutch culture - no longer holds water: on a macro-level, the influence of institutionalized religion has indeed considerably diminished over the last decennia, but the intellectual legacy of Christianity and Christian religious meaning-making are still part of our culture.